The Challenge of Bacterial Strain Identification: Leptospira interrogans Serovars Australis in a Dog and Long-Term Clinical Follow-Up - Tommaso Furlanello; Elisa Mazzotta; Cristina Bertasio; Mario D’Incau; Laura Bellinati; Laura Lucchese; Alda Natale (Tropical Medicine and Infectious Disease)
Leptospirosis is a widespread disease throughout the world, presenting in severe clinical forms in dogs. The pathogenicity of the different serovars in field infections is not fully documented, and clinical diagnosis is often limited to a combination of serological tests and molecular analyses. The latter, although a fundamental tool, cannot identify the infecting strain without further analysis. This study reports the use of various indirect (microscopic agglutination test, MAT) and direct (microbiological culture, real-time PCR) laboratory techniques, followed by typing protocols (Multi-locus Sequence Typing (MLST), Multiple Loci Variable number tandem repeat Analysis (MLVA), serotyping) that allowed for the identification of the Leptospira serovar Australis in a symptomatic and previously vaccinated dog (vaccine containing heterologous strains). This study reports long-term clinical follow-up (0–640 days) and describes the possible role of the infection in the development of chronic renal failure. This study aims to highlight how a combination of different techniques can be useful to better characterise the environmental circulation of zoonotic agents. Therefore, the identification and isolation of circulating L. strains would facilitate the updating of epidemiological data, enhance the knowledge of pathogenicity and long-term clinical effects, and provide a valuable resource for improving the efficacy of a specific serovar vaccination.